Study on the Pasting Properties of Indica and Japonica Waxy Rice - Fang, Sicong; Chen, Cheng; Yao, Yuan; Nsor-Atindana, John; Liu, Fei; Chen, Maoshen; Zhong, Fang (Foods, 2022)
In this study, the physicochemical properties of indica (IWR) and japonica (JWR) waxy rice were investigated to find the critical factor that differentiates the pasting behaviors among the two cultivars. The results showed that the peak viscosity of 5 IWR flours was in the range of 1242 to 1371 cP, which was significantly higher than 4 JWR flours (667 to 904 cP). Correlation analysis indicated that all pasting parameters were not correlated (p < 0.05) with physicochemical properties of rice flours and the fine structure of isolated starches. The pasting profiles of IWRs were still significantly higher than those of JWRs after removing lipid, while there were no significant differences between the two cultivars after removing protein sequentially. Meanwhile, the addition of extracted protein from JWR to the isolated starch significantly decreased the viscosity compared to the addition of protein extracted from IWR. The protein composition results found that the IWR protein contained about 18% globulin and 64% glutelin, while the JWR protein contained 11% globulin and 73% glutelin. The addition of glutelin to isolated starch significantly decreased viscosity compared to the addition of globulin. Therefore, the differences in the content of globulin and glutelin might be the main reasons that differentiate the pasting behaviors of the two cultivars.